An investigation of refractory organics in membrane bioreactor effluent following the treatment of landfill leachate by the O3/H2O2 and MW/PS processes - Chen, Weiming (Waste management (New York, N.Y.), 2019)
Copyright © 2019 Elsevier Ltd. All rights reserved.